Babylon : Mesopotamia and the birth of civilization - Kriwaczek, Paul. (New York : Thomas Dunne Books/St. Martin's Press, 2010)
Historian Kriwaczek (Yiddish Civilization) brings to life the world of ancient Mesopotamia and the city of Babylon, tracing their rise from a loose federation to a monarchy to the rise of ancient Sumerian civilization, with its tales of the Great Flood and the epics of semidivine heroes such as Gilgamesh.
Lessons from the Past : an Introduction -- Kingship Descends from Heaven : The Urban Revolution Before 4000 BCE -- The City of Gilgamesh : Temple Rule between c. 4000 and 3000 BCE -- The Flood : a Caesura in History -- Big Men and Kings : The City-States, c. 3000 to 2300 BCE -- Rulers of the Four Quarters : The Bronze Heroic Age, c. 2300 to 2200 BCE -- Sumer Resurgent : The Dirigiste State, c. 2100 to 2000 BCE -- Old Babylon : The Culmination, c. 1900 to 1600 BCE -- Empire of Ashur : Colossus of the First Millennium, c. 1800 BCE to 700 BCE -- Passing the Baton : an End and a Beginning after 700 BCE.
First published: London : Atlantic Books, 2010.
Includes bibliographical references and index.
Keywords: Iraq -- Civilization -- To 634.; Babylon (Extinct city) -- Civilization; Iraq -- History -- To 634.; Babylon (Extinct city) -- History; Iraq -- Politics and government; Babylon (Extinct city) -- Politics and government